Tahqīq Kitab Bunnatul Jalīs wa Qahwatul Anīs Karya Sayyid Usman bin Yahya: Ingatan Kolektif dan Relevansi Pesan Moral bagi Komunitas Ba‘alawi di Nusantara - Mashudi, Mohamad (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This study examines the manuscript Bunnatul Jalīs wa Qahwatul Anīs authored by Sayyid Usman bin Yahya (d. 1914), the Mufti of Batavia during the Dutch Colonial period, with the aim of making it accessible to a wider audience, particularly the Ba‘alawi community in the Nusantara. The research applies an accurate tahqīq method through traditional philological approaches, supported by the concept of collective memory as proposed by Maurice Halbwachs and later developed by Jan Assmann into the framework of cultural memory. It further analyzes the moral messages articulated in the text. This study differs from the work of Nico J.G. Kaptein, who mainly focuses on Sayyid Usman’s biography and provides only limited discussion of the text, as well as from the study of Naufal Alaf Ramdhan et al., which centers on the issue of ta‘addud al-jum‘ah in his work al-Ajwibah ‘ala Masā’il al-Jum‘ah. The findings reveal that Bunnatul Jalīs wa Qahwatul Anīs functions as a form of cultural memory. A thematic analysis of the 18 chapters in the manuscript identifies four major clusters of moral teachings: personal ethics, social ethics, religious ethics, and intellectual ethics. Sayyid Usman frequently draws on the sayings of classical scholars such as al-Ghazālī and Abū al-Hasan al-Shādhilī, as well as contemporary voices, particularly from the Ba‘alawi tradition itself, including Habīb ʿAbdullāh bin ʿAlawī al-Ḥaddād and Habīb ʿUmar bin Saqqāf. This research highlights the strong relevance of the manuscript to the social dynamics of the Ba‘alawi community in the Nusantara, especially amid current public debates on the role of ḥabāʾib in the digital era. Beyond its value as a literary heritage, the text serves as a living and adaptive instrument of moral advocacy across generations. Keywords: Sayyid Usman, Bunnatul Jalīs, collective memory, moral teachings, Ba‘alawi, manuscript.